THYROID GLAND PARENCHYMA MORPHOLOGICAL ABNORMALITIES IN RATS ON THE THIRD DAY AFTER SKIN THERMAL BURNING - Tiron, O.I.; Dzygal, O.F.; Onufryenko, O.V.; Komlevoi, O.M.; Shapovalov, V.Yu.; Yatsyna, O.I. (World of Medicine and Biology, 2022)
The purpose of the study was to establish thyroid gland histological and ultrastructural changes of experimental animals 3 days after the thermal skin injury under physiological 0.9 % NaCl solution administration. Intrathyroid hemodynamic changes, the stromal component structure alterations and destructive processes in the thyroid gland morpho-functional unit - the follicle - were detected on the microscopic level three days after the animals’ skin experimental thermal injury under the physiological 0.9 % NaCl solution administration. Thyroid gland capsule and stroma throughout this period of the trials were characterized by collagen fibers swelling and focal leukocyte infiltration with segmented neutrophils predominance. Thyroid hemodynamics disturbances were manifested by arterial and venous plethora, stasis in the arterial vessels of the organ and components of the microcirculatory bed. Follicular cells contained a small nucleus with shallow karyolemа invaginations, marginally located heterochromatin and small lumps of it dispersed throughout the karyoplasm. Experimental animals’ thyroid gland hemocapillaries were characterized by both basement membrane components and the endothelial layer swelling as well as stasis of the lumen. Endotheliocytes contained nuclei with heterochromatin peripheral localization. The third day after a skin burn under the physiological 0.9 % NaCl solution administration resulted in certain alterations in the structure of the vascular component of the gland; its stroma and parenchyma were established at the microscopic and submicroscopic level, which could lead to a violation of the secretory cycle of follicular cells and, as a result, to an imbalance in the synthesis and excretion of thyroid hormones. These pathomorphological intrathyroid disorders indicate these micro-changes possible reversibility which is important in terms of such a contingent of patients’ pharmacotherapy.
Keywords: thyroid gland; parenchyma; burning injury; morphological disturbances; hematoxylin-eosin; follicle; thyrocyte; capillary; stasis